The Effect of Ozone Therapy Stimulation on Diabetes Wound Healing Process - Anan Rizky; Dudut Tanjung; Khairunnisa Khairunnisa (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Health problems that are currently developing include diabetes mellitus (DM) with various complications including diabetic ulcers. Diabetic ulcers are the main cause of prolonged pain and even amputation in DM patients. Diabetic wounds are a complication of diabetes that often occurs in the extremities, increasing morbidity and lessens the patient's personal satisfaction. Ozone therapy is one method used to speed up the healing process for diabetic ulcers. This study plans to examine the impact of ozone treatment feeling on diabetic injury mending. The exploration strategy utilizes a semi exploratory technique with a pretest and posttest non-identical benchmark group plan. The testing strategy is a non-likelihood inspecting method.The population in this study were all patients suffering from diabetic wounds who received wound care at the Edwcare clinic in Langsa city.  The respondents of this study were patients suffering from diabetic wounds who received wound care at the Edwacare wound care center in Langsa City, Indonesia  consisting of 28 respondents who received modern wound care dressings and 28 respondents received wound care combined with modern dressings and ozone therapy. The research instrument for assessing wound severity used the Bates-Jensen Wound Assessment Tool. Data analysis used the Friedman and Kruskal Wallis tests. Based on the research results, it was found that there was a more significant effect between wound care using a combination of modern dressings and ozone therapy with a Mean Rank value of 39.75 compared to wound care that only received modern dressing wound care with a Mean Rank value of 17.25 with a value of p -value <0.05. The conclusion is that the effect of ozone stimulation significantly influences the healing process of diabetic wounds and is recommended as a nursing intervention that can be applied in treating diabetic wounds.Keywords:  Diabetes mellitus, diabetic wounds, ozone therapy, stimulation